Loop-mediated isothermal amplification for diagnosis of 18 World Organization for Animal Health (OIE) notifiable viral diseases of ruminants, swine and poultry. (22nd April 2015) - Mansour, Shimaa M. G.; Ali, Haytham; Chase, Christopher C. L.; Cepica, Arnost
Abstract: Loop-mediated isothermal amplification (LAMP) is a simple, powerful state-of-the-art gene amplification technique used for the rapid diagnosis and early detection of microbial diseases. Many LAMP assays have been developed and validated for important epizootic diseases of livestock. We review the LAMP assays that have been developed for the detection of 18 viruses deemed notifiable of ruminants, swine and poultry by the World Organization for Animal Health (OIE). LAMP provides a fast (the assay often takes less than an hour), low cost, highly sensitive, highly specific and less laborious alternative to detect infectious disease agents. The LAMP procedure can be completed under isothermal conditions so thermocyclers are not needed. The ease of use of the LAMP assay allows adaptability to field conditions and works well in developing countries with resource-limited laboratories. However, this technology is still underutilized in the field of veterinary diagnostics despite its huge capabilities.